2020
DOI: 10.36233/0507-4088-2020-65-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of extracts of basidiomycetes and humic compounds substances against Human Immunodeficiency Virus (Retroviridae: Orthoretrovirinae: Lentivirus: Human immunodeficiency virus 1) and Herpes Simplex Virus (Herpesviridae: Simplexvirus: Human alphaherpesvirus 1)

Abstract: Introduction. One of the most urgent problem of modern medicine is the fight against the disease caused by the Human Immunodeficiency Virus (HIV) – HIV infection. The chemical compounds have improved the situation for infected people, but they are toxic, disrupt the metabolism and cannot eliminate the integrated virus from the body. The emergence of resistant HIV strains makes these treatments ineffective. Often, the death of HIV-infected people occurs as a result of the development of opportunistic infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…[ [18][19][20][21][22][23][24] Polyphenol Antioxidant [25] Triterpenoid Anticancer, anti-inflammatory, antiviral, and antioxidant [26][27][28][29][30] Melanin Antioxidant, anti-inflammatory, antiviral, hypolipidemic and immunomodulatory [24,[31][32][33][34] Polysaccharides are natural biopolymers that all living organisms have. And the diversity in monosaccharide composition and structure causes them to have different biological activities [35].…”
Section: Component Biological Activities Referencesmentioning
confidence: 99%
“…[ [18][19][20][21][22][23][24] Polyphenol Antioxidant [25] Triterpenoid Anticancer, anti-inflammatory, antiviral, and antioxidant [26][27][28][29][30] Melanin Antioxidant, anti-inflammatory, antiviral, hypolipidemic and immunomodulatory [24,[31][32][33][34] Polysaccharides are natural biopolymers that all living organisms have. And the diversity in monosaccharide composition and structure causes them to have different biological activities [35].…”
Section: Component Biological Activities Referencesmentioning
confidence: 99%
“…Extracts of I. obliquus also exhibit anti-herpetic activity on herpes simplex virus (HSV)-infected Vero cells (Polkovnikova et al 2014 ; Nosik et al 2020 ), which was found to be mediated by the prevention of HSV entry via action on viral glycoproteins, thus leading to prevention of viral-induced membrane fusion (Pan et al 2013 ). In addition, I. obliquus extracts have antiviral effects on human immunodeficiency virus type 1 (HIV-1) in the lymphoblastoid cell culture MT-4 at concentrations of just 5.0 μg/mL, thus demonstrating its potent antiviral properties (Shibnev et al 2015 ; Nosik et al 2020 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
“…Water extracts from natural I. obliquus inhibit the replication of different strains of influenza virus, herpes virus types 1 and 2, West Nile virus, immunodeficiency virus type 1, and some orthopoxviruses, including variola virus. [11][12][13][14][15][16][17][18][19][20] Natural substances of I. obliquus contain a very wide range of different compounds that are formed in the close interaction of birch and mushroom. 21 These are pigments that form a chromogenic polyphenol-carboxylic complex exhibiting antitumor activity caused by the fact that phenolic compounds regulate the activity of cytoplasmic and mitochondrial ATPases and reduce the formation of ADP.…”
Section: Introductionmentioning
confidence: 99%